Current state and problems of soil fertility preservation in Moldova - Leah, T.G. (AgroChemistry and Soil Science, 2018)
The review article presents actual historical data on the transformation of the land fund structure and soil quality as a result of various types of agrarian reforms in the Republic of Moldova since 1812.The main aspects and consequences of the last agrarian reform of 1991-1996 were described in detail. There are presented actual data demonstrating changes in the use of land resources, which are an argument that the Land Reform in Moldova as a result of an incorrect (confused) strategy has not created the conditions for increasing soil fertility, sustainable land use, increasing agricultural production and, consequently, had a negative impact on the economy of the country due to the massive degradation of soil and ecological resources. The main negative changes in soil quality, nutrient status, physical and biological characteristics are listed. The assessments of existing state programs, ongoing activities and further efforts to prevent and liquidation land degradation in Moldova and address the problem of increasing soil fertility are summarized. Attention is focused on the need to develop special zonal and district programs for the conservation and rational use of available soil fertility, which should be accompanied by serious political support and adequate financing